Dimensi Etis dan Spiritual dalam Praktik CSR pada Panti Asuhan: Implikasi terhadap Pengembangan Akuntansi Sosial - Tenriwaru Tenriwaru (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to examine the ethical and spiritual dimensions in Corporate Social Responsibility (CSR) practices and their implications for the development of social accounting. Despite the growing literature on CSR, most studies remain focused on corporate perspectives and formal disclosure, with limited attention to how CSR is experienced and interpreted by beneficiary stakeholders, particularly in non-profit contexts such as orphanages. This gap highlights the need to explore CSR beyond compliance and reporting, emphasizing its substantive social meaning. This research employs a qualitative approach using a multi-site case study design on orphanages in Makassar as CSR beneficiaries. Data were collected through in-depth interviews, direct observation, and document analysis, and were analyzed using thematic analysis to identify patterns related to ethical and spiritual values in CSR practices. The findings reveal that CSR practices are still largely dominated by short-term and incidental assistance, indicating a gap between formal CSR recognition and the actual needs of beneficiaries. However, when CSR is implemented in a consistent and need-based manner, ethical values such as responsibility, fairness, and accountability, along with spiritual values defined as moral awareness, empathy, and sincerity, become central in shaping meaningful social impact. These dimensions influence not only how CSR is delivered but also how it is perceived and sustained by beneficiaries. This study contributes theoretically by extending social accounting perspectives through the integration of ethical and spiritual dimensions as core elements of social accountability. It challenges the conventional view of CSR as a reporting mechanism and proposes a value-based approach that emphasizes impact, sustainability, and stakeholder-centered accountability. The findings suggest that social accounting should move beyond formal disclosure toward representing the moral and social significance of CSR practices.